Sovereignty Through Technology. - Lan Xinzhen (Beijing Review, 2025)
The article focuses on China's strategic initiatives to enhance its digital economy by improving the efficiency of computing power, algorithms, and data supply. As of June, China has established 10.85 million standard racks and achieved 788 EFLOPS in intelligent computing power, leading the world in large language models with 1,509 released. The central authorities are prioritizing these factors in the 15th Five-Year Plan (2026-2030) to maintain competitiveness in AI development and reduce reliance on foreign technology, particularly in light of U.S. export controls. The aim is to secure digital sovereignty and establish alternative solutions and standards in global digital governance, ensuring that China's population remains connected and protected from external pressures.